Novel thin-film composite reverse osmosis membrane with superior water flux using parallel magnetic field induced magnetic multi-walled carbon nanotubes. (1st January 2020) - Hu, Xuhui; Sun, Jiajin; Peng, Ruichao; Tang, Qiang; Luo, Yunbai; Yu, Ping
Abstract: In this work, magnetic multi-walled carbon nanotubes (MWCNTs) were aligned vertically in thin film nanocomposite (TFN) reverse osmosis (RO) membranes. Magnetic MWCNTs were synthesized by in situ co-precipitation of MWCNTs, Fe 2+ and Fe 3+ . Meanwhile, a parallel magnetic field created by two ferrite magnets was used to align magnetic MWCNTs. To simulate the magnetic field, the computer software COMSOL-Multiphysics® was applied. In order to demonstrate the impact of parallel magnetic field, two groups of TFN RO membranes (Group A and Group B) were prepared. Before the phase inversion process, polymer solutions of Group A were treated in the parallel magnetic field for 2 min, while polymer solutions of Group B were exposed to air for 2 min. As a result, under magnetic field, magnetic MWCNTs were aligned vertically on the polysulfone surface, and provided efficient water transport channels. The optimized membrane with 0.7 wt% magnetic MWCNTs of Group A obtained remarkable water flux of 11.389 L m −2 h −1 while maintaining high NaCl rejection. The results indicated that a simple and efficient method to improve water flux of TFN RO membranes was successfully developed. Highlights: Magnetic multi-walled carbon nanotubes were prepared by in situ co-precipitation. Magnetic multi-walled carbon nanotubes were added into polysulfone layers. A parallel magnetic field was applied to align magnetic carbon nanotubes. Software of COMSOL-Multiphysics® was used to simulate the parallel magnetic field. The optimal reverse osmosis membranes showed superior water flux.